Determinan Intensitas Energi di Indonesia - Kartiasih, Fitri; Syaukat, Yusman; Anggraeni, Lukytawati (UI Scholars Hub, 2012)
This study contributes to the existing literature by examining energy consumption, energy intensity and its determinants in Indonesia's aggregate and sectoral economy. Index Ideal Fisher uses to decompose two key determinants of changes in energy intensity - efficiency improvements and changes in economic activity - to analyze which determinant is more important in driving improvements in energy intensity. VAR/VECM analysis is used to determine which economic variables affect the aggregate intensity. The study found that energy intensity increased gradually. The main contributing factor in the national level is the changes in economic activity, while in the sectoral level is efficiency effect.